Do policy makers take grants for granted? The efficacy of public sponsorship for innovative entrepreneurship - Stevenson, Regan; Kier, Alexander S.; Taylor, Shannon G. (Strategic Entrepreneurship Journal, 2021)
Abstract Research Summary We investigate the short‐ and long‐term effects of public sponsorship in the form of grants on venture growth and subsequent investment funding. We adopt a temporal approach and assess our results using discontinuous growth modeling. This approach allows us to unpack the complexity of sponsorship interventions and provide insights into how quickly, how long, and under what conditions grants augment growth. Using a proprietary sample of 129 ventures located in eight incubators, we find that securing an initial grant increases the rate at which ventures acquire private investment capital but not revenue over time. We draw on resourcefulness theory and signaling theory and explore the moderating role of venture size. We discuss our contributions to the entrepreneurship and public policy literatures. Managerial Summary Are public grants effective at sparking entrepreneurial growth? To deepen our understanding of public policies that are designed to promote innovative entrepreneurship, we investigate the short‐ and long‐term effects of new venture grant sponsorship. We study 129 ventures located in eight business incubators over a 4‐year period. Our results indicate that although there are initial advantages to receiving a grant, there are also potential shortcomings as grant receipt does not directly influence long‐term revenue growth. We theorize that having abundant access to grant capital reduces the ventures need to “stretch” resources and grow revenue over time. Yet, initial grants seem to signal to investors that the venture represent a “good bet” as investment trajectories follow the opposite growth pattern, increasing steadily over time.